الحق في سلامة الجسد في ظل جائحة كورونا - عامر، آلاء محمد فيصل إسماعيل (جامعة المنوفية - كلية الحقوق, 2023)
• بعد أن استخرت الله قمت بعمل هذا البحث الحق في سلامة الجسد فى ظل جائحة "كورونا" ومضمونه المقصود بالحق في سلامة الجسد وماهية فيروس "كورونا". • أثر جائحة "كورونا" على الحق في سلامة الجسد كالحق في الرعاية الطبية والحق في الخصوصية. • دور المنظمات الدولية لحماية الحق في سلامة الجسد في ظل جائحة "كورونا". • الجهود المبذولة من النظم القانونية لحماية الحق فى سلامة الجسد فى ظل جائحة "كورونا". • After I asked God for help, I did this research on the right to the safety of the body in light of the Corona pandemic and its content what is meant by the right to the safety of the body and what the Corona virus is. • The impact of the Corona pandemic on the right to bodily integrity, such as the right to medical care and the right to privacy. • The role of international and regional organizations to protect the right to body integrity in light of the Corona pandemic. • Efforts made by legal systems to protect the right to bodily integrity in light of the Corona pandemic.
Keywords: السلامة الجسدية -- جائحة كورونا "كوفيد-19" -- الرعاية الطبية -- الحياة الخاصة -- القانون المصري